To the issue of forecasting price dynamics in the property valuation - Gnennyi, O. N. (Science and Transport Progress, 2012)
The problems of short-, medium- and long-term forecasting price dynamics are considered. The improvement of short-term forecasting techniques based on exponential smoothing is proposed. A modified autoregressive model of the first-order differences for the medium-term forecasting is developed. A method of constructing the approximating function of the first-order differences as a linear combination of trigonometric functions, which can be used for long-term forecasting, is proposed.